Correlates of Socio Economic Status with Domestic Water Consumption Pattern in Chitrakoot District (U.P.) - Yadav, Swati; Singh, Usha (National Geographical Journal of India, 2022)
Domestic fresh water is a fundamental requirement for human welfare. The study determines the relationship of domestic water use with socio economic and other factors at household level in the plain and plateau area of Chitrakoot district. The main aim of this study is to improve the understanding of how local communities in the district relate to water, based on questionnaires and interview survey of 800 respondent from both the areas of plain and plateau. The study has examined the respondent’s daily activity-wise water consumption, sources of water, distance of different water sources and frequency of water supply. The study remarked that the percapita daily water consumption for the area is found to be 74.52 litres per person per day with a standard deviation of 41.14. Water consumption was found to be correlated with socioeconomic factors like monthly per capita income, caste, source of water, distance of water source and time to collect water.